Application of Cooperative Learning Method Field Market Type to Improve Students Learning Outcomes in the Subject Pkwu At Sman 2 Kuta Baro - Dewi, Rosmala; Nurbaiti; Yanti, Yeni Irma; Maryam, Siti; Fitriana (MultiTech Publisher, 2024)
This research focuses on the application of Field Market type cooperative learning method to improve the activeness and cognitive learning outcomes of students in Class XI Social Studies in the subject of Workshop and Entrepreneurship. The purpose of the study was to evaluate the effectiveness of Field Market type cooperative learning method in improving students' learning outcomes, as well as to observe the changes that occur in the level of student activeness after the application of the method. This research is a type of classroom action research, involving students of Class XI Social Studies as the research subjects. Data on student activeness was collected through observation during the learning process, while data on student learning outcomes was obtained through tests conducted before and after the application of this method. The results showed a significant increase in student activeness during the learning process after the application of the Field Market method. In addition, students' cognitive learning outcomes also showed improvement after this method was applied. The results of independent sample T-test showed that there was a significant difference in students' learning outcomes before and after the application of Field Market cooperative learning method. This finding indicates that Field Market cooperative learning method is effective in increasing students' active participation and supporting the achievement of better learning outcomes. Thus, this method can be relied upon as an effective and relevant approach to be applied in the learning of Workshop and Entrepreneurship.